2004
DOI: 10.1063/1.1689293
|View full text |Cite
|
Sign up to set email alerts
|

Thermodynamics of β-amyloid fibril formation

Abstract: Amyloid fibers are aggregates of proteins. They are built out of a peptide called β-amyloid (Aβ) containing between 41 and 43 residues, produced by the action of an enzyme which cleaves a much larger protein known as the Amyloid Precursor Protein (APP). X-ray diffraction experiments have shown that these fibrils are rich in β-structures, whereas the shape of the peptide displays an α-helix structure within the APP in its biologically active conformation. A realistic model of fibril formation is developed based… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
2

Year Published

2004
2004
2013
2013

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 28 publications
(30 citation statements)
references
References 28 publications
(25 reference statements)
0
28
2
Order By: Relevance
“…While our results agree with the previous simulations, [10][11][12] in that β-hairpins constitute a significantly populated conformational ensemble, we observe some discrepancy regarding details of the structural nature of Aβ12-28. In particular, the β-turn seen in the present work is located at positions L17V18F19F20, which represents a two residue shift along the sequence toward the N terminus with respect to the β-turn of the earlier simulations.…”
Section: Discussioncontrasting
confidence: 66%
See 2 more Smart Citations
“…While our results agree with the previous simulations, [10][11][12] in that β-hairpins constitute a significantly populated conformational ensemble, we observe some discrepancy regarding details of the structural nature of Aβ12-28. In particular, the β-turn seen in the present work is located at positions L17V18F19F20, which represents a two residue shift along the sequence toward the N terminus with respect to the β-turn of the earlier simulations.…”
Section: Discussioncontrasting
confidence: 66%
“…In particular, the β-turn seen in the present work is located at positions L17V18F19F20, which represents a two residue shift along the sequence toward the N terminus with respect to the β-turn of the earlier simulations. [10][11][12] We note that the β-hairpins sampled in these simulations were visited in our simulations (with a C α RMS∼2 Å from the most representative state †) but they were not populated significantly. In addition, the temperature-dependence of the hairpins seen here differs from that seen by the same authors, who reported a non-monotonic tem-perature-dependence.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phys. (2004) [26]) and with several theoretical and experimental hypotheses on how monomers must be organized in the fibril (Daidone, Proteins: Structure, Function and Bioinformatics, 2004, in press).…”
Section: Simulation 4smentioning
confidence: 98%
“…A great deal of attention in recent literature has been devoted to the study peptide Ab(1-42), responsible for the deposition in human brains of plaques causing Alzheimer's disease, and fragmentes of Ab(1-42) which retain the ability of forming fibrils like Ab (12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27)(28). Molecular dynamics (MD) simulations have been used to investigate the molecular properties of selected fragments.…”
Section: Introductionmentioning
confidence: 99%